Faktor-Faktor Penyebab Menurunnya Motivasi Belajar Remaja - Amniar Ati; Fitriyani Saudi (Jurnal Penelitian Pendidikan Geografi, 2025)
Adolescence is a crucial phase in education because at this age students experience a search for identity, social adjustment and character formation. This study aims to identify the factors causing the decline in learning motivation of adolescents in Togomangura village. This type of research is a survey. The sample in this study amounted to 30 peoples. The data collection technique used is a questionnaire. The data analysis technique used is descriptive analysis to describe the frequency of respondents based on the answers that have been filled in. The results of the study showed that the intrinsic factors of decreasing learning motivation of adolescents in Togomangura village include; a) no passion and desire to succeed, b) no parental encouragement, and c) no hopes and ideals for the future. While the extrinsic factors include; a) use of social media, b) online games, and c) the existence of a non-conducive learning environment.